Correlation of body size with body weight of Etawa crossbreed (PE) goats of the Kaligesing type in Pamekasan Regency - Shamad, Zulfaini; Widyanand, Cepryana Sathalica; Hidayati, Nurul (Politeknik Negeri Jember, 2024)
The population of goats in East Java especially in Madura is the Etawa crossbred [PE] goat type Kaligesing, the goat is in great demand because has a larger body proportion than the Kacang goat which is native to Indonesia goat. The purpose of this study was to determine the performance of Kaligesing type PE goats using the correlation of body size with body weight in Pamekasan Regency, Madura. This research was conducted in smallholder farms in four villages (Panaguan, Larangan Dalam, Larangan Luar, and Montok) of Larangan sub-district, Pamekasan regency. The material used was 60 Kaligesing type PE goats aged 1-1.5 years (Poel 1) and 1.5-2.5 years (Poel 2). The research method used was a case study and sampling using the purposive sampling method. The results showed that gender had a very significant effect (P<0.01) on body size and body weight in Poel 1 and Poel 2. The correlation between body size (body height, body length, chest girth, body weight) and body weight of Kaligesing-type PE goats Poel 1 and Poel was 2 0.88; 0.96; 0.97 for P1 and 0.80; 091; 0.97 for Poel 2, respectively. The conclusion of this study is that body size can be used to estimate body weight in Kaligesing type PE goats.